Designing Students’ Writing Skill with the Help of the LEB Android Application - Ulfa Wulan Agustina; Siti Syafa'ah (APPLICATION: Applied science in Learning Research, 2021)
Language ability consists of four abilities to master it. The four abilities are speaking, listening, writing, and reading. Speaking can be done spontaneously, but writing must be planned and organized. The purpose of this research is to design an appropriate android application-based learning media to help students develop their English writing skills. This study uses the Research and Development method which was adapted in the development of the ADDIE model. The researcher designed a learning media called "Learn English Better". This learning media has been validated by media experts and material experts before being tried out on students. The data collection instruments used were questionnaires and interviews. The results of media validation obtained a value of 84,6, for material validation a value of 76,36 was obtained, and the results of the implementation of this media obtained a value of 73,2. Based on the results above, the researcher concludes that the Learn English Better android application is suitable for use in MA Al-Asy'ari.